MEDIA LITERASI SEBAGAI UPAYA PENGUATAN KESADARAN PENGARUH NEGATIF MEDIA DIGITAL TERHADAP ANAK – ANAK - zahra, Latifa; Ajy Waskyto Sugiyanto, bagus (Jurnal Ilmiah Padma Sri Kreshna, 2019)
The Sophistication of digital media provides how easy to access about information in almost all aspects of society. The leap of technological sophistication is too rapid makes the negative impact of digital media increasingly disguised. This community service aims to improve the understanding of housewives regarding the negative impact of digital media on children. Using the adult approach method, this service activity actually looks for cases from within the community itself, and guides the community to find solutions to problems from themselves. At the end of the activity, it was known that housewives in the Demen, Pakem, Sleman area had knowledge of the negative impact of digital media on children, but awareness of its long-term impact still became homeworks not only for the mothers themselves, but also the other stakeholders.